Tes Diagnostik Pelajar BIPA Tingkat Pemula: Rancangan Pengembangan Spesifikasi Uji, Stimulus tes, dan Kisi-Kisi - Mega Pratiwi; Titik Harsiati; A. Syukur Ghazali (Graduate School of Universitas Negeri Malang, 2021)
Abstract: Diagnostic tests in language learning such as BIPA are very important. That's because the function of the diagnostic test is to get a diagnosis of learning difficulties. BIPA students often have difficulty learning Indonesian, especially beginner level students. Therefore, a diagnostic test in BIPA learning is very necessary. This study aims to provide a design related to the development of test ability specifications, test stimuli, and the development of a diagnostic test grid for listening, reading, and writing skills that are suitable for beginner level BIPA students. The research method used is a literature study. The findings of this study are a conceptual step-by-step design related to the development of a diagnostic test for entry-level BIPA students.Abstrak: Tes diagnostik dalam pembelajaran bahasa seperti BIPA sangat penting. Hal itu dikarenakan fungsi dari tes diagnostik adalah untuk mendapatkan diagnosa kesulitan belajar. Pelajar BIPA sering mengalami kesulitan belajar bahasa Indonesia terutama pelajar tingkat pemula. Oleh karena itu, adanya tes diagnostik dalam pembelajaran BIPA sangat diperlukan. Penelitian ini bertujuan untuk memberikan rancangan terkait pengembangan spesifikasi kemampuan uji, stimulus tes, dan pengembangan kisi-kisi tes diagnostik kemampuan menyimak, membaca, dan menulis yang sesuai untuk pelajar BIPA tingkat pemula. Metode penelitian yang digunakan adalah studi literatur. Temuan penelitian ini adalah rancangan pijakan konseptual terkait pengembangan tes diagnostik untuk pelajar BIPA tingkat pemula.